2009
DOI: 10.1097/shk.0b013e318193cb52
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Procalcitonin for Outcome Prediction in Unselected Postoperative Critically Ill Patients

Abstract: The importance of postoperative procalcitonin (PCT) measurements for outcome prediction is currently controversial. Conflicting results have been obtained for patients after polytrauma, sepsis, peritonitis, or cardiac surgery and may result from incomplete adjustment for important confounders or from nonlinear PCT effects. We retrospectively analyzed the association of PCT concentration with postoperative mortality, morbidity, and length of stay in an unselected series of 220 consecutive patients who required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 29 publications
3
23
1
Order By: Relevance
“…Moreover, taking into account the diverse variables that can influence mortality, the performance of a multivariate analysis is a key aspect to detect those parameters independently associated with death. These are two different aspects of this work when compared to other studies that have demonstrated the importance of PCT (or other biomarkers) as a prognostic variable [3841,43]. Also, it is remarkable that PCT values represent the host response after a bacterial insult.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, taking into account the diverse variables that can influence mortality, the performance of a multivariate analysis is a key aspect to detect those parameters independently associated with death. These are two different aspects of this work when compared to other studies that have demonstrated the importance of PCT (or other biomarkers) as a prognostic variable [3841,43]. Also, it is remarkable that PCT values represent the host response after a bacterial insult.…”
Section: Discussionmentioning
confidence: 89%
“…In postoperative critically ill patients, the cutoff point for PCT concentration was 1.44 ng/mL to detect worse outcome [44], which may be due to infection and possible unsuccessful control of the source.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, several investigators have reported high levels of CRP among patients with burn injury with or without septic complications (16, 20, 21). CRP has also been shown to have a poor predictor of mortality compared to other biomarkers (22, 23). …”
Section: Markers Of Acute Inflammatory Responsementioning
confidence: 99%